Registration of 'Comrade' peanut. Issue 3 (12th August 2022) - Chamberlin, Kelly; Bennett, Rebecca S.; Isleib, Thomas George; Copeland, Susan; Dunne, Jeffrey C.
Abstract: 'Comrade' (Reg. no. CV‐149, PI 698820) is a large‐seeded, high‐oleic, virginia‐type peanut ( Arachis hypogaea L. subsp. hypogaea var. hypogaea ) with enhanced pod size distribution and seed size compared with the virginia‐type cultivar 'Contender'. Released jointly by the USDA‐ARS and North Carolina State University in 2021, Comrade (tested as N15022olEJ and NCEX17) is a high‐oleic virginia breeding line resulting from a selection made from the cross N06007E/3/X05248(BC1F1:F04), Bailey//X05027 (F01), Bailey/N02060ol. Comrade had an average pod yield of 5, 260 kg ha –1, a total sound mature kernel (TSMK) of 69%, a sound mature kernel (SMK) weight of 97 g 100 seed –1, and 62% extra‐large kernels (ELKs), giving it the highest estimated value per hectare among the virginia‐type cultivars tested in Oklahoma for 2018–2020. When entered in the national Uniform Peanut Performance Test, Comrade performed well in all locations, averaging 5, 235 kg ha –1, 84% fancy pods, 44% ELKs, an SMK weight of 103 g 100 seed –1, and a TSMK of 68%. Comrade's average super jumbo pod count per kilogram and average pod brightness score were reported at 317 kg –1 (9 per ounce) and 50, respectively, indicating large, bright pods, which are necessary components of any market‐worthy virginia‐type cultivar. Comrade consistently averaged 47–50% super jumbo pods across locations in Oklahoma and nationwide trials. This significant increase in the percentage of super‐jumbo pods compared with currently grown cultivars will increase growers' profits and enable producers in the southwestern United States to increase participation in the foreign export market. Core Ideas: Comrade has enhanced pod size distribution, giving it a high export market value. Comrade was the potential cultivar with the highest value per hectare in Oklahoma during 2018–2020. Comrade performed well in all peanut‐producing states included in the Uniform Peanut Performance Tests.